Examining intercultural differences in close friendship maintenance on Facebook: a relational dialectics perspective - Tengku Siti Aisha Tengku Mohd Azzman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Close friendship is a crucial and distinctive interpersonal tie that can survive a lifetime. Maintaining such friendships at a satisfactory level, even with the aid of social networking websites (SNS) such as Facebook, can be a challenging process. Previous research has shown that relationship satisfaction among close friends depends both upon relationship maintenance strategies (e.g., positivity, openness, supportiveness) and the management of dialectical contradictions (e.g., openness-closeness and autonomy-connection). Furthermore, cultural differences may also dictate how individuals choose to maintain close friendships online. Therefore, guided by the relational dialectic perspective, a key objective of this research was to determine whether the role of Facebook in friendship maintenance differs significantly across two cultures: the U.S. and Malaysia. All participants completed an online survey in which they were asked to think of a close friend with whom they communicated both face-to-face and on Facebook. Among others, findings showed that Malaysian respondents perceived their close friends as using certain maintenance strategies (i.e., positivity, interaction planning, openness, social information seeking, and avoidance) significantly more often than did Americans. Culture also influenced how relational dialectics moderate the relationship between maintenance strategies and relationship satisfaction among close friends. The implications of the findings for the role of Facebook in close friendship maintenance across culture, and the relational dialectics theory will be discussed.